Ferns with important ethnomedicinal value and chemical and biological aspects of Nephrolepis cordifolia: brief review - Jaciel Gonçalves dos Santos; Cassia Cristina Fernandes; Mayker Lazaro Dantas Miranda (Acta Scientiarum. Biological Sciences, 2024)
The Atlântic Forest comprises native forest formations which make it one of the main biomes in Brazil while the Cerrado is a strategical biome due to its diversity and economic resource. Ferns play important roles in both ecosystems and in the social context. Even though there are few studies of Pteridophytes, they have become fundamental not only to phytoremediation, but also to chemical and pharmaceutical industries. Ferns have different forms of life since they may be terrestrial, epiphytic, rupicolous, aquatic, hemiepiphyte and climbing plants which range from tiny herbaceous plants to arborescent ones. Nephrolepis cordifolia (L.) C. Presl, which is mostly found in the world’s tropical and subtropical regions, is an ornamental fern that belongs to the Nephrolepidaceae family and whose young fronds and tubers are edible in some countries. Besides, it has medicinal properties against certain diseases, such as rheumatism and anorexia, and symptoms, such as nasal congestion. This brief report aims at compiling results of studies of chemical and biological applications of ferns, mainly the ones exhibited by the N. cordifolia species, such as the main secondary metabolites it biosynthesizes, its lab-proven biological activities and its uses in folk medicine.